2022
DOI: 10.1051/0004-6361/202243162
|View full text |Cite
|
Sign up to set email alerts
|

Coronal mass ejection followed by a prominence eruption and a plasma blob as observed by Solar Orbiter

Abstract: Context. On 2021 February 12, two subsequent eruptions occurred above the western limb of the Sun, as seen along the Sun-Earth line. The first event was a typical slow coronal mass ejection (CME), followed ∼ 7 hours later by a smaller and collimated prominence eruption, originating south of the CME, followed by a plasma blob. These events were observed not only by the SOHO and STEREO-A missions, but also by the suite of remote-sensing instruments on board Solar Orbiter. Aims. We show how data acquired by the F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 75 publications
1
9
0
Order By: Relevance
“…One possible condition is that the included angle between the electric field direction of the observed current sheets and the LOS one is small enough, and thus the projection widths of the current sheets depend mainly on the narrow line-like region (e.g., Figure 5(a)). Furthermore, the observed current sheet is an emission-enhanced region (Chae et al 2017;Patel et al 2020), and the emission intensity is related to the plasma temperature or density (Plowman & Caspi 2020;Bemporad et al 2022). For the region where the magnetic reconnection is violent, more plasma flows are introduced into the reconnection layer and more magnetic field energy is released to heat the plasmas (Mackay et al 2010;Takasao et al 2012), which contributes to a brightened region of strong emission (Humphries & Morgan 2021;Cheng et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…One possible condition is that the included angle between the electric field direction of the observed current sheets and the LOS one is small enough, and thus the projection widths of the current sheets depend mainly on the narrow line-like region (e.g., Figure 5(a)). Furthermore, the observed current sheet is an emission-enhanced region (Chae et al 2017;Patel et al 2020), and the emission intensity is related to the plasma temperature or density (Plowman & Caspi 2020;Bemporad et al 2022). For the region where the magnetic reconnection is violent, more plasma flows are introduced into the reconnection layer and more magnetic field energy is released to heat the plasmas (Mackay et al 2010;Takasao et al 2012), which contributes to a brightened region of strong emission (Humphries & Morgan 2021;Cheng et al 2023).…”
Section: Discussionmentioning
confidence: 99%
“…From a comparison between the VL and UV emission distributions across the blob, Bemporad et al (2022) concluded that the emission in the UV Lyα line is mostly due to the collisional rather than radiative excitation of H atoms. Moreover, from the apparent different location of the blob in the VL and UV channels, it was inferred that the plasma temperature across the blob is not uniform, but is larger at the base of the blob and then decreases from the bottom to the top of the blob.…”
Section: Available Observationsmentioning
confidence: 99%
“…Moreover, from the apparent different location of the blob in the VL and UV channels, it was inferred that the plasma temperature across the blob is not uniform, but is larger at the base of the blob and then decreases from the bottom to the top of the blob. The additional heating could be provided by magnetic reconnection that occurs just below the blob being responsible also for its observed acceleration (see Bemporad et al 2022, for more details). Unlike other events reported in the literature, only one blob was observed propagating along the post-CME CS in this case.…”
Section: Available Observationsmentioning
confidence: 99%
“…Large-scale solar eruptive activities are the principal cause of extreme space weather in Earth and planetary space environments (Švestka, 2001;Cheng et al, 2014;Lugaz et al, 2017;Gopalswamy et al, 2018). Different kinds of large-scale solar eruptions, including prominence/filament eruptions (Li et al, 2016;Jenkins et al, 2018;Fan, 2020;Devi et al, 2021), flares (Chen et al, 2015;Li et al, 2016;Cheung et al, 2019), and coronal mass ejections (CMEs, Shen et al, 2014;Lamy et al, 2019;Bemporad et al, 2022), are generally considered to be different manifestations of the eruptions of coronal magnetic flux rope (Zhang et al, 2001;Vršnak et al, 2005;Jiang et al, 2016;Chen et al, 2020;Liu, 2020). Therefore, investigating the initiation and evolution of flux rope eruptions is crucial not only for understanding solar eruptions, but also for space weather forecasting.…”
Section: Introductionmentioning
confidence: 99%